Resistance Level and Enzyme Activity of Spodoptera litura F. to Chlorpyrifos and Their Sensitivity to the Oil Formulation of Azadirachta indica Juss. and Cymbopogon nardus (L.) Rendl. - R. Arif Malik Ramadhan; Neneng Sri Widayani; Danar Dono; Yusup Hidayat; Safri Ishmayana (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
This study aimed to obtain resistance information of S. litura from Karangpawitan and Lembang districts (West Java, Indonesia) against chlorpyrifos insecticides (200 g/l) and their sensitivity to oil mixture of A. indica and C. nardus (1:1) using feeding and topical assay. The activity of acetylcholinesterase, esterase, and glutathione s-transferase from S. litura larvae in both populations were tested to determine their role in insect resistance. Results showed that S. litura population from Lembang had a higher level of resistance to chlorpyrifos compared to Karangpawitan. The sensitivity of the two S. litura populations had a relatively similar resistance ratio (RR) value of less than 1 to botanical insecticide. These indicated that resistant population could be controlled by a mixture of this botanicals insecticide. Enzyme activity test indicated that chlorpyrifos at a concentration of 0.26% could inhibit the acetylcholinesterase activity of insect population from Karangpawitan by 98.66% while those from Lembang, it was only 35.31%. Specific activity of esterase from Karangpawitan was 13.37 units/mg while Lembang population was 119.65 units/mg. The specific activity of the Glutathione S-Transferase (GST) of Karangpawitan population was 1140.82 units/mg while Lembang population was 793.73 units/mg. The high activity of the three enzymes could be responsible for resistance of S. litura larvae to chlorpyrifos.